Re-considering Job - Newsom, Carol Ann (Currents in biblical research, 2007)
Although recent scholarship on Job has tended to approach the book from interpretive stances that are at some distance from traditional historical-critical verities, the classic historical-critical questions about the unity of the book continue to dominate the way questions are posed. Hermeneutical disputes about the book focus on interpreters’ decisions to find a way to preserve a resistant Job, or to advocate for an interpretation of the divine speeches that makes comprehensible a Job who ‘sees’ in a new way, and so is willing to renounce his alienation. A new direction of Joban scholarship focuses on the reception history of the book.